Pengembangan Branding Pariwisata Maluku Berbasis Kearifan Lokal - Noviawan Rasyid Ohorella; Edy Prihantoro (Program Studi Ilmu Komunikasi, 2021)
Tourism is a driver of Indonesia's economic growth to encourage GDP growth, increase the intensity of international trade, and increase global investment. The Maluku government must prepare maximum concrete steps in developing tourism based on local wisdom. This study aims to analyze destination branding based on local wisdom. The research uses a qualitative approach. Data were collected through participant observation, in-depth interviews, and focus group discussions. To enrich the data, the researchers also used data extracted from the documentation. The results showed that the Maluku tourism strategy in carrying out tourism branding based on local wisdom was indicated by the use of the tourism tagline The Spice Islands. In addition, the Maluku government elaborates between tourist attractions and cultural attractions, and strengthens brandidentity and local identity. Keywords: branding, local identity, local wisdom, tourism.